THE USE OF INTERACTIVE STUDYING METHODS IN TEACHING OPERATIVE SURGERY AND TOPOGRAPHIC ANATOMY - V.M. Fedorak (Ukrainian Medical Stomatological Academy, 2015)
One of the main requirements of credit-modular system of studying at medical schools is improving the quality of training of future doctors, because patients' lives depend on their knowledge and skills. That's why the department along with traditional methods is using new teaching methods. It is very important for the balance to be observed between theoretical knowledge with practical skills and operational technique. The aim of this study was to determine the role of traditional methods of practical skills development combined with modern methods. In teaching operative surgery the most important thing is the formation of students' practical skills. We know that they can be obtained in the process through frequent repetition and characterized by a high level of studying, the lack of conscious-element of control and regulation. These are actions that by repeating are brought up to automatism. Accordingly, the measure skills formation is the action without thinking of how it should be performed. While studying operative surgery in order to increase the motivation to master the practical skills a part of most lessons is conducted by using interactive methods for classic type of business or role play. Surgical team is formed for working. Students receive tasks regulated by guidelines, and then they stand near the operating table and perform the task. However, they are guided by the instruction, which consists of algorithm of performing certain surgical techniques or operations. In addition, student may receive not only simple task, but the task with a situational problem. There are developed case studies on issues that require discussion and grounding of decision, which allows using this method of interactive training. During the discussion, with the participation of teacher, students widely use tables, models, tools and other visual aids. With sufficient mastery of operative techniques, at the end of discipline mastering is carried out on an experimental basis to one department where aseptic and antiseptic conditions of operation are performed on the animal. While performing training operations student must seamlessly know instruction in order to carry it out according to the received role. However, on the ground of current laws it's totally impossible to obtain cadaveric material and organs of dead people, and strict requirements of Bioethics Commission on the use of animals in education led to a strong reduction of lessons performed on animals. All this led to search for innovative types of theoretical material and practical skills. Recently, the department began using multimedia presentations not only during lectures but during practical lessons. During practical lessons by using multimedia projector videos show some operational techniques and operations, which greatly improve the perception of the material. In the class of interactive learning students can improve their knowledge using advanced interactive applications from anatomy, clinical anatomy and operative surgery using program "The surgeon-simulator". For in-depth study of the most important units of operative surgery at Department elective courses are developed and will be introduced in the educational process: "The surgical technique", "Technology of surgeries", "Urgent surgery." Thus, the usage of interactive methods in studying of operative surgery and topographic anatomy greatly helps in mastering theoretical material and as well as practical skills, increases motivation and interest in learning of discipline. The usage of interactive applications on anatomy, clinical anatomy, operative surgery program "The surgeon simulator" helps students in mastering both theoretical material and practical skills.